Вплив комплексних модифікаторів на структуру чавунів з різним вмістом сірки - Іванова, Людмила; Колотило, Євген; Хитько, О. Ю.; Терехін, В. О. (Physico-technological Institute of Metals and Alloys, 2023)
The results of research and refinement of the technology of application of complex modifiers in rolling mill production are given. This study was preceded by a study of the features of the modifying effect of individual rare earth metals on the parameters of crystallization and structure formation of cast iron at different cooling rates that occur in the real roll form. It was found that the minimum required amount of modifier to achieve the maximum level of temperature reduction of the beginning of eutectic crystallization depended on the cooling rate. Increasing the cooling rate led to a shift of this amount of modifier towards lower concentrations. The study was performed in the laboratory on cast iron with different sulfur content (0.031 and 0.092 %). After melting and heating cast iron in a silite furnace, the calculated amount of complex modifier and ferrosilicon was introduced into the melt. The oven was turned off and the sample was cooled with the oven (Vcool. = 10 °C/min). Thus, the chemical composition of cast iron before modification was constant. As the value of the additive of the complex modifier decreased, the amount of silicon added decreased, and therefore together with cast iron the calculated amount of ferrosilicon was loaded in the quartz crucible, so that the amount of silicon in cast iron was constant. After cooling, the samples were cut and the structure and shape of graphite inclusions were examined at half radius. For modification, two different complex modifiers based on rare earth metals were used, which were obtained by the aluminothermic method. The range of concentrations of modifiers 1.75–3.0 wt% was investigated. The results of quantitative and metallographic analyzes showed that complex modifiers based on rare earth metals can provide high-strength cast iron with spherical graphite when used to modify melts with high sulfur content. The interval of residual contents (additive values) was established, which ensured the production of cast iron with spherical and compact forms of graphite inclusions. When modifying high-sulfur roll iron, complex modifiers did not provide spherical cast iron with graphite inclusions. To enhance the spheroidizing effect of the modifier, magnesium must be added to its composition. The intervals of contents of rare earth metals at modification by complex modifiers which provided reception of high-strength cast iron with spherical form of graphite inclusions are established.